2006
DOI: 10.1002/per.599
|View full text |Cite
|
Sign up to set email alerts
|

Who shapes the self of independents and interdependents? Explicit and implicit measures of the self's relatedness to family, friends and partner

Abstract: We suggest that social relationships shape the self in different ways, depending on whether persons define themselves as independent or interdependent. While the self of independents is most strongly associated with mental representations of others to whom they are related because of their own deliberate action (e.g. friends), the self of interdependents is most strongly connected with representations of others with whom they share allocated group memberships (e.g. family members). We took both explicit (Study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 46 publications
2
26
1
Order By: Relevance
“…In our sample, the roommates did not know each other before living together and were not allowed to choose each other. In this case, the type of relationship in our sample was not voluntary (or acquired, in the terms of Pohlmann & Hannover, 2006), but it was also not allocated like a family relationship.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…In our sample, the roommates did not know each other before living together and were not allowed to choose each other. In this case, the type of relationship in our sample was not voluntary (or acquired, in the terms of Pohlmann & Hannover, 2006), but it was also not allocated like a family relationship.…”
Section: Discussionmentioning
confidence: 87%
“…Recent research on how different types of relationships shape the self, however, sheds light on why this unexpected relationship may have occurred in our sample. Pohlmann and Hannover (2006) examined perceptions of relationships among individuals with independent and interdependent self-construals. They found that independents perceived the self to be most closely connected to individuals that they had freely chosen to be connected to, such as friends.…”
Section: Discussionmentioning
confidence: 99%
“…Belongingness can be achieved by strengthening bonds with familiar others (e.g., family members) or by forming bonds with strangers (Baumeister & Leary, 1995;Pöhlmann & Hannover, 2006). We wondered which form of belongingness uncertainty drove these finding, and we conducted Experiment 2 to find out.…”
Section: Forms Of Uncertainty and Procedural Fairness 17mentioning
confidence: 99%
“…Importantly, these needs can be satisfied not only through affiliation with familiar others (e.g., family members, friends) but also through affiliation with strangers (e.g., interacting with a fan at a sporting event, starting a conversation with a pub patron) (Baumeister & Leary, 1995;Pöhlmann & Hannover, 2006 The main objective of Experiment 2 was to clarify the concept of belongingness uncertainty and its link with the enacted organizational procedures. We induced general uncertainty, as in Experiment 1, for the purpose of replication, and we also induced family-belongingness uncertainty and stranger-belongingness uncertainty.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Edlund [31] and Nordenfelt [32]. Social interaction is the base for developing one's sense of self and self-consciousness, and the social context can be interpreted as something that offers the opportunity to shape one's identity and awareness [34,35]. For people suffering from dementia, their perceptions of their own life, telling their life story, was interpreted as a vital aspect of their sense of identity [36,37].…”
Section: Discussionmentioning
confidence: 99%